Human Rights With Emphasis on Prisoner Rights: The Growing Significance of Prisoner Rights in Human Rights Law (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In the past two decades, Human Right Law has attainedcrucial importance in the universe and as in demand as never before. With theadvancement the rights of prisoners have also grown manifold which in past wasa discarded and deserted subject.